Akulturasi Agama terhadap Budaya Indonesia - Eva Iryani (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Indonesia is a country that has a strong enough religion. From a wide variety of religions in indonesia. Islam is the largest religion in indonesia. Formerly known as the indonesia archipelago which hindhu-budha is the religion adhered. When islam came to the archipelago hindhu religion-Buddhism slowly started to disappear so that islam is Growing rapidly with ease. The development of Islam in indonesia resulted in adjustments to the nusantara culture against islam which acculturation. Islamic culture and acculturation are seen in indonesia against building relics, calligraphy, dance, and much more. Even now the relics still lowered hereditary, so still we can see that acculturation can still be keenly felt and seen consciously or unconsciously. Acculturation itself is a social process that arises from a group with a particular culture are confronted with elements from a foreign culture. This concerns the acculturation of mixing culture with the Islamic religion, which is still associated with a culture which is not left behind his trademark, causing experience typical of a new one.